Information communication technology learning through the broadband learning center to build ‘Smart Community’ - Nurul Ratna Sari (Masyarakat, Kebudayaan dan Politik, 2019)
This research identifies the implementation of the Broadband Learning Center (BLC) program of the Surabaya government as a facility for community learning on Information Communication Technology (ICT). BLC is one of the crucial developments in building Smart Community as the main actor in Surabaya Smart City establishment. In the Surabaya context, BLC is one of the foundations in establishing a smart city which is an integration of three main dimensions, namely BLC as ICT facilities, community as the actor in smart city development, and the Surabaya government. The study applied a qualitative method with a descriptive research type — data collected through in-depth interviews, observations, and documentation studies. Interviews were conducted to 22 informants, which consisted of one BLC coordinator in government institution, one representation of BLC coordinator from community, and eight facilitators in five parts of the city areas which provided BLC facilities, and 12 representations of community groups as the users that consisted of adolescent and youth, women, and senior community. The observation was being held in BLC spots, while community learning activities occurred. The BLC remarkably facilitates community learning and education in dealing with ICT. The study indicates that the program performs ICT community learning which establishes community ability to understand and to use information from digital sources. However, it has been challenged by the conception of digital literation in boosting smart community active participation, which should enable the community to connect and interact with, also utilize the information. A socio-technical learning approach can be pertinently implemented by linking social and technological factors in order to fit the learning process and targeted community and also widen its opportunity in achieving smart community sustainability.